Serial reversal learning in nectar-feeding bats - Shambhavi Chidambaram; Sabine Wintergerst; Alex Kacelnik; Vladislav Nachev; York Winter (Animal Cognition)
Abstract We explored the behavioral flexibility of Commissaris’s long-tongued bats through a spatial serial reversal foraging task. Bats kept in captivity for short periods were trained to obtain nectar rewards from two artificial flowers. At any given time, only one of the flowers provided rewards and these reward contingencies reversed in successive blocks of 50 flower visits. All bats detected and responded to reversals by making most of their visits to the currently active flower. As the bats experienced repeated reversals, their preference re-adjusted faster. Although the flower state reversals were theoretically predictable, we did not detect anticipatory behavior, that is, frequency of visits to the alternative flower did not increase within each block as the programmed reversal approached. The net balance of these changes was a progressive improvement in performance in terms of the total proportion of visits allocated to the active flower. The results are compatible with, but do not depend on, the bats displaying an ability to ‘learn to learn’ and show that the dynamics of allocation of effort between food sources can change flexibly according to circumstances.